Challenges in Facilitating Modular Instruction in Sulu AMIDST Covid-19 Pandemic - Jawali, Anang Fatma T (International Journal of Membrane Science and Technology, 2023)
The COVID-19 pandemic has had an unheard-of effect on the educational system. One of the projects used as a type of distant learning that makes use of self-learning modules is modular learning. This descriptive-correlational study compared the blended instructional strategy in Sulu to online and modular methods to determine the number of implementation issues. While the t-Test for Independent Samples determined the significant differences as to the Gender, One-way Analysis of Variance (ANOVA) determined the significant differences when data were grouped according to age, civil status, length of service, and education. Frequency counts and percentages determined the respondent’s profile; mean and standard deviation determined the extent of subsumed categories, such as technological, individual, domestic, institutional, and community barriers. A high positive correlation was found between the challenges affecting the delivery of the blended instructional approach and the Pearson Product Moment Correlation Coefficient (Pearson r). As a result, difficulties with delivering the mixed educational approach in Sulu became apparent. The results of this study tend to support the Baticulon, Ronie E. et al. (2020) Model of Barriers (Technological, Individual, Domestic, Institutional, and Community barriers) to blended learning in the COVID-19 period, which was based on Howlett D. et al. (2009) Integration of a case-based online module.